Direct and indirect effects of coaching leadership style on athlete engagement - Li, Jingjing; Xing, Suxuan (Frontiers in Psychology, 2025)
IntroductionThis study examines how coaching leadership styles influence athlete engagement through the sequential mediating mechanisms of perceived social support and achievement goal orientation.MethodsUsing validated psychological scales, the research explores the interplay between democratic and authoritarian leadership approaches, athletes’ perceptions of social support, and their task- or ego-oriented goal pursuits.ResultsThe findings reveal that democratic leadership significantly enhances athlete engagement by fostering a supportive environment that strengthens perceived social support, which subsequently promotes task-oriented goals. This dual pathway highlights the critical role of social support and mastery-focused motivation in cultivating athlete engagement. In contrast, authoritarian leadership does not demonstrate meaningful associations with engagement or its mediators.DiscussionThe results underscore the importance of democratic leadership in creating a psychologically empowering climate, offering actionable insights for coach development programs to emphasize autonomy-supportive and collaborative strategies. Theoretically, the study bridges Self-Determination Theory and Achievement Goal Theory by demonstrating how socially embedded support systems and task-oriented goals synergistically contribute to optimizing athlete performance and well-being.